202k views
1 vote
Explain your answer!!!!!!

Explain your answer!!!!!!-example-1
User IDanil
by
5.0k points

1 Answer

5 votes

Remark

If you just focus on the gray ones for a moment.

The series goes up 0 2 4 6

6 is in the fourth figure so you can count by figures.

f(n) = 2*(n - 1) So for the fourth figure, for example, you get f(4) = 2*(4 - 1) = 2 * 3 = 6 which is just what we see.

So far, the nth figure is f(n) = 2*(n - 1) But there is still 1 red one to account for.

Now we get f(n) = 2(n - 1) + 1 or 2n - 2 + 1 or 2n - 1.

Answer: f(n) = 2n - 1 <<<<< answer

User Hanachronism
by
5.8k points